Anemia prevalence and severity among pregnant refugee women settled in the West Nile region, Uganda - Felix Bongomin; Winnie Kibone; Ritah Nantale; Sarah Lebu; Byron Awekonimungu; Phillip Musoke; Daniel S. Ebbs; Rachel Beardsley; Chimdi Muoghalu; Stephen Ochaya; Musa Manga (PLoS ONE, 2025)
Background Anemia during pregnancy is a significant global public health issue, associated with adverse outcomes for both the mother and the newborn. While the prevalence and impact of anemia in pregnancy have been well-documented in general populations, the burden and severity of anemia among pregnant refugee women particularly those residing in the West Nile region of Uganda, remain unknown. Our study aimed to determine the prevalence and severity of anemia in this specific population to address this critical knowledge gap. Methods Between 1st April and 30th June 2023, we conducted a cross-sectional study among pregnant women attending the antenatal care clinic at 3 health centers serving the refugee communities in Adjumani district, Uganda. Anemia in pregnancy was defined as a hemoglobin (Hb) level of < 11.0 g/dl and microcytosis as a mean corpuscular volume of < 76 fL. Multivariable logistic regression was done to assess for the independent predictors of anemia in pregnancy. Data were analyzed in Stata version 15.0. Results We enrolled 304 participants. The mean age of the participants was 25.4 years with a standard deviation of 4.9 years. The prevalence of anemia was 52.6% (95% CI 46.9–58.4). Of these, 85 (28.0%) were classified as mild, 73 (24.1%) moderate, and 2 (0.7%) had severe anemia. The median Hb was 10.8g/dL (10.1–11.7). Forty-one (25.6%) of those with anemia had microcytosis. Having at least a secondary/tertiary education level (aOR: 1.51, 95%CI: 0.98–1.78, p < 0.001), being single (aOR: 1.77, 95%CI: 1.53–1.93, p < 0.001) and parity >4 (aOR: 1.51, 95%CI: 0.98–1.78, p < 0.001) were associated with higher odds of having anemia. Conclusions Anemia in pregnancy is prevalent among pregnant refugee women in the West Nile Region of Uganda. Our findings suggest the need for targeted interventions such as health education about the consequences of anemia, promotion of early antenatal care (ANC) attendance, and provision of iron and folate supplementation during pregnancy, to potentially reduce the burden of anemia in this vulnerable population.